Outcomes of Small Incision Lenticule Extraction with Dual-Incisions in Myopic Patients - Abdelwahab S (Dove Medical Press, 2020)
Shereef Abdelwahab,1 Abdelmonem Hamed,1 Ahmed Elshahat,1 Soliman Rashad,2 Maha Elfauyomi1 1Benha University, Benha, Egypt; 2Suez Canal University, Ismailia, EgyptCorrespondence: Abdelmonem Hamed Tel +20 1221640288Email abdelmonem.abdelmonem@fmed.bu.edu.egPurpose: To assess the stability, safety, predictability, and efficacy of small incision lenticule extraction (SMILE) with dual-incisions in myopic patients.Setting: Ebsar Eye center, Benha, Qalyopia, Egypt.Design: Single-center, retrospective, COHORT study.Patients and Methods: The study was conducted as a retrospective non-comparative analysis of the records of 105 eyes of 53 patients treated by the SMILE with a dual-incisions technique for a mean spherical myopic error of − 5.05 ± 1.93 D (range: − 1.38 to − 9.0 D) with or without astigmatism and the mean astigmatism of − 0.90 ± 0.83 D. The mean LogMAR corrected distance visual acuity (CDVA) was − 0.04 ± 0.07.Results: One month after surgery, the mean refractive error was − 0.03 ± 0.56 D (range: 0.88 to − 1.50 D), and the mean postoperative astigmatism was 0.20 ± 0.31 D. The mean LogMAR UDVA was 0.07 ± 0.18 in the last follow-up visit, 12 months after surgery. At the end of the follow-up period, approximately 91.43% of patients had unchanged CDVA or gained one or more lines, 8.57% lost one line of CDVA, and 0.0% lost 2 lines.Conclusion: SMILE with dual-incisions is effective and safe, with a stable and predictable outcome for correction of myopia and myopic astigmatism.Keywords: SMILE, ReLEX, SMILE technique, kerato-refractive, LASER vision correction, small incision lenticule extraction